Humans and climate change in the middle and lower Yellow River of China. (30th June 2019) - Su, Kai; Kidder, Tristram R.
Abstract: The relationship between climate changes and human responses has been hotly debated. This paper expands this topic by reviewing and presenting case studies in the middle and lower Yellow River, Henan and Shandong provinces. We first review the paleoenvironmental data of both regions and then use the Sanyangzhuang site, Henan, and the Chengziya and Jiaojia sites, Shandong, as examples of human activities and sedimentary histories. Comparisons between the paleoenvironmental and archaeological data reveal that the changes in human occupation at these sites did not occur synchronously with climatic and paleoenvironmental changes. On the one hand, human activities were influenced by extreme climate-related events such as floods. However, humans also show great resilience by returning to the same sites or continuing cultivation at the same sites. Changes in temperature and precipitation did not result in settlement abandonments. On the other hand, human activities ceased to exist in periods of land and climate stabilities. With their increasing capacity to modify landscapes through time, human decisions and activities become equally important as climate change.